The Effect of the Deans Model on Mental Motivation and Learning the Skills of Receiving Transmissions and Preparing Volleyball - Nassr Abdulrazzaq; Sufyan Latif Mahmoud; Riyadh Mashaan; Akram Rashid; Hussein Ali Suleiman (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Identify the effect of the Deans model on improving students' mental motivation compared to students who learn by the methods used, measuring the extent to which the Deniz model affects learning the skills of preparation and receiving volleyball transmissions. The researchers used the experimental method, and the research sample included students of the College of Physical Education and Sports Sciences at the University of Anbar for the academic year 2024/2025, numbering (40) students; the following research tests were used for the purpose of achieving the research objectives Test the skill of receiving the transmission of the arms from the bottom, testing the skill of preparation from the top with the fingers, mental motivation test The skill tests and mental motivation were conducted after the research sample was completed after it completed the implementation of the program, and at the same time, the method and conditions in which the pre-tests were conducted.  The following statistical parameters were used. Calculates both the percentage values and the mean. And standard deviation. Torsion coefficient and T-test for correlated samples. Through the analysis of the evidence and its statistical processing, it was found that the values of (T) calculated for the test of the skill of receiving the transmitter, preparation, and mental motivation are all significant values when compared to the tabular value of (2.02) at the degree of freedom (39) and the level of significance (0.05). The research results showed that applying the Deniz model had a significant positive effect on mental motivation. It increased students' motivation and self-motivation, which contributed to improved mental performance and concentration during performance. The study also showed that using the Deniz model in training had a major role in improving the skills of receiving transmissions and preparation in volleyball. The ability to receive transmissions with greater accuracy has improved, allowing the ball to be directed more effectively for setup.